2022
DOI: 10.3389/fgene.2022.966939
|View full text |Cite
|
Sign up to set email alerts
|

Genomic surveillance unfolds the SARS-CoV-2 transmission and divergence dynamics in Bangladesh

Abstract: The highly pathogenic virus SARS-CoV-2 has shattered the healthcare system of the world causing the COVID-19 pandemic since first detected in Wuhan, China. Therefore, scrutinizing the genome structure and tracing the transmission of the virus has gained enormous interest in designing appropriate intervention strategies to control the pandemic. In this report, we examined 4,622 sequences from Bangladesh and found that they belonged to thirty-five major PANGO lineages, while Delta alone accounted for 39%, and 78… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 47 publications
1
2
0
Order By: Relevance
“…The global d N /d S ratio in the SARS-CoV-2 genome during the pre-vaccination period was calculated as 0.48 ± 0.06, thus indicating a purifying selection pressure. The observed value is similar to previous studies showing that SARS-CoV-2 genome depicts overall purifying selection pressure ( 61 63 ) amd study reporting overall SARS-CoV-2 genome dN/dS of around 0.55 ( 61 ). The d N /d S ratio increased to 0.99 ± 0.11 in the post-vaccination period in various demographic regions, suggesting SARS-CoV-2 genomes showing overall neutral selection.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The global d N /d S ratio in the SARS-CoV-2 genome during the pre-vaccination period was calculated as 0.48 ± 0.06, thus indicating a purifying selection pressure. The observed value is similar to previous studies showing that SARS-CoV-2 genome depicts overall purifying selection pressure ( 61 63 ) amd study reporting overall SARS-CoV-2 genome dN/dS of around 0.55 ( 61 ). The d N /d S ratio increased to 0.99 ± 0.11 in the post-vaccination period in various demographic regions, suggesting SARS-CoV-2 genomes showing overall neutral selection.…”
Section: Resultssupporting
confidence: 90%
“…A continuous trend of positive selection was identified in S in all the three phases. Previous studies during the year 2020 have identified ORF10 to be under strong positive selection, along with ORF3a, ORF8 and N also depicting much higher number of d N ( 62 , 67 , 68 ). ORF8 is involved in host-pathogen interactions through its nine encoded proteins ( 69 ), ORF3a is involved in interference with host ion channels by encoding viroporin ( 70 ), while overexpression of ORF10 is known to downregulate IFN-1 expression, leading to suppression of the antiviral innate immune response ( 71 ).…”
Section: Resultsmentioning
confidence: 92%
“… 40 Our results corroborates with the findings of the one of the earlier studies from Bangladesh which reported that the AY.122 lineage increased significantly from September 2021 while B.1.617.2 was declining. 41 The 20J clade of Gamma variant and 21D clade of the Eta variant were found to be circulating in Bangladesh for only 2–3 months (March to June, 2021) with relatively lower prevalence (<5.0%) than other clades. The Gamma variant is associated with a higher degree of transmissibility.…”
Section: Discussionmentioning
confidence: 94%